Organocatalytic Additions to C=X Bonds (X=O, C, and NR) - Zhang, Zhiguo; Justus Liebig University Giessen (My University, 2008)
In the present doctoral thesis, a series of novel chiral thiourea derivatives was firstly designed and synthesized, and their potential applications as organocatalysts were widely investigated in several important synthetic transformations, such as transfer hydrogenation of aldimines, biomimetic reduction of nitroolefins, cyanosilylation of ketones, and hydrophosphonylation of imines. Since the newly designed thiourea-based catalysts were generally inefficient for the promotion of reduction with trichlorosilane, various amino acids derived N-formamides were developed for the asymmetric reductions of ketimines using trichlorosilane as the hydrogen donor. The main results of this dissertation can be summarized as follows: Chapter 3 describes our efforts in organocatalytic reductions: 3.1 challenging reported results from another group, we first reported that thiourea derivatives can catalyze transfer hydrogenation of aldimines through hydrogen bonding activation with Hantzsch ester as the hydrogen source. 3.2 describes a thiourea-catalyzed biomimetic reduction of nitroolefins with Hantzsch ester as the hydrogen donor, which may provide insights into the mechanism of redox reactions in biological systems. 3.5 a series of novel proline based N-formamides was firstly synthesized and characterized. Their catalytic efficiencies were investigated in asymmetric reductions of ketimines with trichlorosilane as the hydrogen source. In chapter 4, we firstly demonstrated that the asymmetric addition of TMSCN to ketones can be promoted by one chiral module involving thiourea and anion moieties. In addition, n-BuLi was found to be an efficient agent for initiating this transformation. In chapter 5, a one-pot three component addition of carbonyls, amines, and diethyl phosphite was found to proceed smoothly under neat conditions without catalysts and solvents. Moreover, the possibility of autocatalysis for the asymmetric addition of diethyl phosphite to imine was also investigated with kinetic and preparative methods.

Im Rahmen dieser Dissertation wurden zahlreiche neue chirale Thioharnstoffderivate dargestellt und deren mögliche Anwendung als Organokatalysatoren für verschiedenste Reaktionen, wie zum Beispiel in der Transferhydrierung von Aldiminen, der biomimetischen Reduktion von Nitroolefinen, der Cyanosilylierung von Ketonen und Hydrophosphonylierung von Iminen untersucht. Da sich die dargestellten Thioharnstoff-basierten Katalysatoren als generell inaktiv für die Reduktion mit Trichlorsilan zeigten, wurden verschiedene von Aminosäuren abgeleitete N-Formamide synthetisiert und diese in der asymmetrischen Reduktion von Ketiminen, mit Trichlorsilan als Wasserstoffquelle, eingesetzt. Die wichtigsten Ergebnisse dieser Dissertation können wie folgt zusammengefasst werden: In Kapitel 2 wird organokatalytische Reduktion dargestellt: 3.1 auf der Grundlage von bereits veröffentlichten Ergebnissen anderer Arbeitsgruppen wird beschrieben, wie ein zweifach substituierter Thioharnstoff die Transferhydrierung von Aldiminen über H-Brücken Katalyse beschleunigt. Hierbei dient der Hantzsch-Ester als Wasserstoffquelle. 3.2 beschreibt die Thioharnstoff-katalysierte, biomimetische Reduktion von Nitroolefinen mit Hantzsch-Ester als Wasserstoffquelle. Diese Reaktion kann das Verständnis von Redoxmechanismen in biologischen Systemen verbessern. 3.3 stellt die Darstellung von einer Bibliothek von neuen N-Formamiden vor. Deren katalytische Effizienz wurde für die asymmetrische Reduktion von Ketiminen mit Trichlorsilan als Wasserstoffquelle untersucht. In Kapitel 4 konnten wir erstmals zeigen, dass die asymmetrische Addition von TMSCN an Ketone durch ein chirales Katalysatorsystem, welches das Thioharnstoffmotiv und einen anionischen Rest enthält, beschleunigt werden kann. Zusätzlich zeigte sich n-BuLi als effizienter Initiator dieser Umsetzung. In Kapitel 5 wird die Ein-Topf-Drei-Komponenten-Synthese von Carbonylverbindungen, Aminen und Diethylphosphit unter lösungsmittel- und katalysatorfreien Bedingungen beschrieben. Weiterhin wurde die Möglichkeit der Autokatalyse für die asymmetrische Addition von Diethylphosphit an Imine mit experimentellen Methoden untersucht.
Organokatalytische Addition von C=X Bindungen (X=O, C, und NR)
Keywords: Organokatalyse; Thioharnstoffe; Reduktion; Addition; N-formamid; Organocatalysis; Thiourea; Reduction; Addition; N-formamide; ddc:540